The Emergency Severity Index (version 3) 5-Level Triage System Scores Predict ED Resource Consumption - Tanabe, Paula; Gimbel, Rick; Yarnold, Paul R; Adams, James G (Journal of emergency nursing, 2004)
The Emergency Severity Index (ESI) version 3 is a valid and reliable 5-level triage instrument that is gaining in popularity. A unique component of the ESI algorithm is prediction of resource consumption. Our objective was to validate the ESI version 3 triage algorithm in a clinical setting for the following outcome measures: actual resource consumption and patient length of stay in the emergency department and hospital. We conducted a retrospective, descriptive study of 403 ED patients who presented to a large academic medical center. The following dependant variables were abstracted from the ED record: number of ED resources used and emergency department and hospital length of stay. The relationship between ESI level and each of the dependent variables was determined. Mean resource use decreased monotonically as a function of ESI level 1 (5), 2 (3.89), 3 (3.3), 4 (1.2) and 5 (0.2). The ED average length of stay (minutes) per ESI level was as follows: 1 (195), 2 (255), 3 (304), 4 (193), and 5 (98). ESI triage level did not predict hospital length of stay. The ESI algorithm accurately predicted ED resource intensity and gives administrators the opportunity to benchmark ED length of stay according to triage acuity level.